2021
DOI: 10.1038/s41598-021-02505-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative meta-omics for identifying pathogens associated with prosthetic joint infection

Abstract: Prosthetic joint infections (PJI) are economically and personally costly, and their incidence has been increasing in the United States. Herein, we compared 16S rRNA amplicon sequencing (16S), shotgun metagenomics (MG) and metatranscriptomics (MT) in identifying pathogens causing PJI. Samples were collected from 30 patients, including 10 patients undergoing revision arthroplasty for infection, 10 patients receiving revision for aseptic failure, and 10 patients undergoing primary total joint arthroplasty. Synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…One of the cited criticisms related to the use of NGS is that it is unable to distinguish between active and treated infections, as genetic material may persist in the joint even after bacterial cell lysis [107,108]. Notwithstanding, a recent study from our institution explored this issue and found that the presence of DNA correlated with the presence of RNA (and active infection) in majority of patients with and without PJI [100]. Based on these findings, one is inclined to assume that the presence of any DNA in patients with PJI could be indicative of an active infection.…”
Section: Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the cited criticisms related to the use of NGS is that it is unable to distinguish between active and treated infections, as genetic material may persist in the joint even after bacterial cell lysis [107,108]. Notwithstanding, a recent study from our institution explored this issue and found that the presence of DNA correlated with the presence of RNA (and active infection) in majority of patients with and without PJI [100]. Based on these findings, one is inclined to assume that the presence of any DNA in patients with PJI could be indicative of an active infection.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…This RNA-based sequencing method offers a deeper insight on the clinical relevance of identified organism(s) in any given specimen, since active virulence and antimicrobial-resistance mechanisms can be determined [99]. Goswami et al [100] recently performed a comparison of 16S rRNA, MG and MT sequencing methods and showed that MT most accurately differentiated between primary, aseptic revision and PJI cases, concurrently revealing a greater number of resistance genes with higher concordance compared to MG sequencing.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…The high performance (sensitivity and specificity) of SMg has been recently highlighted for the etiological diagnosis of a number of infectious diseases ( Miao et al, 2018 ; Filkins et al, 2020 ; Gu et al, 2021 ; Miller and Chiu, 2021 ), including bone and joint infections ( Street et al, 2017 ; Thoendel et al, 2018 ; Gamie et al, 2021 ; Goswami et al, 2021 ), meningitis and encephalitis ( Wilson et al, 2019 ; Rodino et al, 2020 ), or necrotizing fasciitis ( Rodriguez et al, 2020c ). Indeed, by allowing the detection and quantification of an unlimited panel of microorganisms, including bacteria, viruses, fungi, or parasites without a priori orientation, SMg is capable to identify the etiology of any infectious disease, including those due to microorganisms that have never been previously described in human infections ( Rodriguez et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, NGS-based approaches, as shotgun metagenomics (SMg) or amplification of the universal bacterial 16S rRNA gene and NGS sequencing of the PCR products (NGS 16S), appear to be particularly promising. Focusing on SMg, recent studies have demonstrated its utility for the etiological diagnosis of infections ( Miao et al, 2018 ; Filkins et al, 2020 ; Gu et al, 2021 ; Miller and Chiu, 2021 ), including meningitidis/encephalitis ( Wilson et al, 2019 ; Rodino et al, 2020 ), necrotizing soft-tissue infections ( Rodriguez et al, 2020c ), pneumonia ( Hilton et al, 2016 ; Zhou et al, 2021 ), bloodstream infections ( Grumaz et al, 2016 ), bone and joint infections ( Street et al, 2017 ; Thoendel et al, 2018 ; Gamie et al, 2021 ; Goswami et al, 2021 ) or fever with unknown origin ( Fu et al, 2022 ). Moreover, because SMg has the capacity to generate the full-length sequence of bacterial genomes (unlike 16S approaches), this method could be used for the study of antimicrobial susceptibility and molecular typing.…”
Section: Introductionmentioning
confidence: 99%
“…While MG is a comprehensive method that randomly sequences DNA to detect all microbes present in a sample, it is unable to differentiate between latent and active microbial communities. In clinically relevant settings, MT has been shown to be a promising method in its ability to identify active pathogens and antimicrobial-resistance mechanisms ( Goswami et al., 2021 ; Malone et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%